Learning Participation of Learners in Athletic Materials at SMP Negeri 1 Halong - Maris, Rizky Syawaldi; Amirudin, Akhmad; Arifin, Ramadhan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of student learning participation in athletic materials at SMP Negeri 1 Halong. This study uses a quantitative descriptive method. The research population is 41 students in the 8th grade of SMP Negeri 1 Halong. The sampling technique used purposive sampling with a sample of 25 students. The instrument used is a questionnaire with a Likert scale that has been validated by experts. Data analysis uses percentage descriptive statistics to determine the level of student participation. The results showed that 9 students were 36% in the "medium" category, 7 students were 28% "high", 5 students were 20% "low", 3 students were 12% "very low", and 1 student 4% was "very high" in athletic material learning participation. It can be concluded that the majority of students have varying levels of involvement in athletic sports learning. This research also provides the perspective that obstacles such as low motivation and inadequate facilities can be overcome with more creative teaching techniques, teacher support, and a conducive school atmosphere.